Nurses' knowledge and management of incompatibility issues in intravenous pharmaceutical preparations - Erna Prasetya Ningrum; Marlyn Dian Laksitorini; Endang Lukitaningsih; Fita Rahmawati (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Administering multiple intravenous (IV) preparations through a single catheter line can lead to incompatibility issues, such as precipitation. Precipitation can be avoided with sufficient knowledge by nurses during the administration of IV preparations to patients. This research aims to assess nurses' knowledge and management of incompatibility issues in IV pharmaceutical preparations. This non-experimental research collected data through interviews with healthcare professionals (nurses). The research was conducted at Sultan Agung Islamic Hospital, Semarang. A total of 14 healthcare professionals (nurses) who reconstituted and administered IV pharmaceutical preparations to patients in the Intensive Care Unit (ICU) participated in the research. The results revealed that 13 nurses (92.9%) encountered incompatibility incidents with seven types of drugs. Five nurses (29.4%) reported incompatibility issues with cefoperazone. The most frequently observed incompatibility was color change, reported by seven nurses (53.8%), such as white spots appearing during phenytoin reconstitution and discoloration in IV pharmaceutical preparations of cefoperazone and ceftriaxone. The most common approach to addressing incompatibility was replacing the preparation, reported by six nurses (46.2%). The management of incompatibility issues varied among nurses, even when dealing with the same pharmaceutical preparation. Therefore, training on sterile preparation incompatibility should be provided to all healthcare professionals to establish a standardized operational procedure (SOP) for handling incompatibility in IV pharmaceutical preparations.